2005
DOI: 10.1016/j.jacc.2005.02.061
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blinded, Placebo-Controlled Multicenter Trial of Adenosine as an Adjunct to Reperfusion in the Treatment of Acute Myocardial Infarction (AMISTAD-II)

Abstract: Clinical outcomes in patients with STEMI undergoing reperfusion therapy were not significantly improved with adenosine, although infarct size was reduced with the 70-microg/kg/min adenosine infusion, a finding that correlated with fewer adverse clinical events. A larger study limited to the 70-microg/kg/min dose is, therefore, warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
282
1
15

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 528 publications
(300 citation statements)
references
References 39 publications
2
282
1
15
Order By: Relevance
“…The use of intravenous adenosine after primary coronary stenting reduced the infarct size [627]. Clinical outcomes in patients with acute MI undergoing reperfusion therapy (thrombolysis) were not significantly improved with adenosine infusion (3-h infusion of 50 or 70 μg/kg/min) [628]. However, it was reported later that continuous infusion of adenosine for 3 h improved left ventricular function and reduced infarct size in patients with ST-segment elevation MI [629].…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…The use of intravenous adenosine after primary coronary stenting reduced the infarct size [627]. Clinical outcomes in patients with acute MI undergoing reperfusion therapy (thrombolysis) were not significantly improved with adenosine infusion (3-h infusion of 50 or 70 μg/kg/min) [628]. However, it was reported later that continuous infusion of adenosine for 3 h improved left ventricular function and reduced infarct size in patients with ST-segment elevation MI [629].…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…However, so far there are no data from large-scale clinical trials or from more selective adenosine receptor ligands. In addition, a large-scale trial where adenosine was administrated as an adjunct to reperfusion in the treatment of acute myocardial infarction concluded that adenosine did not prevent the development of heart failure but was able to significantly reduce the infract size (Ross et al, 2005). Parkinson's disease is also another example of pathology where targeting of the adenosine receptors seem to have a therapeutic potential (Lopes et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…31) Nicorandil is a hybrid of a mitochondrial ATP-dependent potassium channel (mK ATP ) opener and nitric oxide. Nicorandil can augment ischemic tolerance of myocytes and coronary microvasculature because it can mimic and/or augment ischemic preconditioning (IPC).…”
Section: Medical Treatmentmentioning
confidence: 99%